Green supply chain management practices: direct effects sustainability performance - Rizki, Adam Firman; Augustine, Yvonne (Technium Social Sciences Journal, 2022)
Purpose research to determine about effect Green Supply Chain Management to Sustainability Performance from manufacturing companies in Indonesia. This quantitative study was conducted on 222 manufacturing companies in Indonesia, consisting of 148 manufacturing companies registered with IDX and 74 non-IDX manufacturing companies. The findings showed that ten hypotheses are green purchasing, green manufacturing, green marketing, and also internal environment has no effect to sustainability performance. While Green Distribution, Eco Design, environmental education, Investment Recovery, Customer cooperation, and Green Information system have positive and significant impacts to Sustainability Performance. The originality of this research is the addition of measurement indicators on sustainability performance from ISO 26.000, Indonesia regulation from Environment and Forestry Minister number: P.75/MENLHK/SETJEN/KUM.1/102019 regarding roadmap and waste reduction by many producers.